Beyond ratification: a critical review of Malaysia’s implementation of the UNESCO anti-doping convention - Chin, Jeremy Jason Chwan Chuong; Tan, Ling Ling (Frontiers in Political Science, 2025)
Malaysia’s 2006 ratification of the UNESCO International Convention against doping in sport emphasized its commitment to advancing clean sport through robust national legal and policy frameworks. This review critically evaluates Malaysia’s subsequent implementation of the convention, specifically evaluating the establishment and operational role of the Anti-Doping Agency of Malaysia (ADAMAS), the alignment of national anti-doping rules with the World Anti-Doping Code, and the engagement of key governmental and sports institutions. Employing a systematic review methodology, the study synthesizes and analyses legislative texts, official reports, longitudinal testing data, and recent enforcement cases to evaluate the nation’s progress. The paper highlights significant national achievements, including expanded out-of-competition testing, the establishment of structured disciplinary procedures, and growing public awareness initiatives. Nevertheless, persistent challenges remain, notably a reliance on foreign laboratories, an over-reliance on urine-based testing, inherent resource limitations, and inconsistent compliance among national sports associations. The review concludes by proposing targeted recommendations designed to strengthen national anti-doping capacity, promote sustainable practices, and reinforce Malaysia’s crucial position as a regional advocate for clean sport.